Sustainable management methods: performance assessment in large companies - Machado, M. J. C. V. (2018)
The general objective of this study is to contribute to the understanding of the performance evaluation methods used by large companies. As specific objectives we have the following: to identify the methods used and the importance attributed to them; to analyse their implementation process and the level of success given to it. The data collection method used was a survey to the financial managers of the largest companies in Portugal, which resulted in thirty-five valid responses. The main contributions of this study were the associations found between the following variables: the method used and the level of importance assigned to it; the person in charge of implementing the method and training provided to employees; the method used and the degree of success attributed to its implementation; the degree of resistance to change and the degree of success in implementing the performance evaluation method.